In vitro invasiveness and antimicrobial resistance of Salmonella enterica subspecies isolated from wild and captive reptiles. (2nd March 2021) - McWhorter, Andrea; Owens, Jane; Valcanis, Mary; Olds, Liberty; Myers, Cecilia; Smith, Ian; Trott, Darren; McLelland, David
Abstract: Reptiles are carriers of Salmonella and can intermittently shed bacteria in their faeces. Contact with snakes and lizards is a source of human salmonellosis. Here, two populations of reptiles, wild and captive were surveyed for Salmonella . One hundred thirty wild‐caught reptiles were sampled for Salmonella including 2 turtle, 9 snake and 31 lizard species. Fifty‐two of 130 (40%) animals were Salmonella positive: one of 5 (20%) turtles, 7 of 14 (50%) snakes and 44 of 111 (39.6%) lizards. One hundred twenty‐two reptiles were sampled from a zoo collection including 1 turtle, 6 tortoise, 9 lizard, 14 snake and 1 crocodile species. Forty‐two of 122 (34.4%) captive reptiles sampled were Salmonella positive. Salmonella was most commonly isolated from lizards and snakes. Fifteen serotypes were identified from zoo and 19 from wild‐caught reptiles and most were members of subspecies enterica (I), salamae (II), arizonae (IIIa) or diarizonae (IIIb). Antimicrobial susceptibility testing was conducted on all Salmonella isolates; only two exhibited resistance, a Salmonella subsp. (II) ser. 21:z10 :z6 (Wandsbek) isolate cultured from a wild‐caught reptile and a Salmonella Typhimurium DT120 isolated from a captive snake. The invasive capacity of reptile‐associated Salmonella strains into cultured human intestinal epithelial (Caco2) and mouse macrophages cell lines (J774A.1) was also investigated. All isolates were invasive into both cell lines. Significant (P ≤ 0.001) variability in invasiveness into polarized Caco2 cells was observed. Salmonella Eastbourne exhibited the highest invasiveness into Caco2 cells and Salmonella Chester the lowest, with mean per cent recoveries of 19.99 ± 0.32 and 1.23 ± 0.30, respectively. Invasion into J774A.1 macrophages was also variable but was not significant. Salmonella subsp. II ser. 17:g, t:‐ (Bleadon) exhibited the highest invasiveness into J774A.1 with a mean per cent recovery of 10.19 ± 0.19. Thus, reptile‐associated Salmonellae are likely to have different capacities to cause disease in humans.